(untitled) (Revista Contexto & Educação, 2026)
The present study aims to understand interprofessional learning and territorialities in the educational journey of students participating in the Programa de Educação pelo Trabalho para a Saúde – PET-Saúde Interprofissionalidade, developed at a university in eastern Minas Gerais. The investigation is grounded in a qualitative and interdisciplinary approach, with a theoretical foundation in the studies of Bernard Charlot, Paulo Freire, and authors who discuss interprofessional education and the concept of territory in health. The “knowledge balance” was used as a data collection tool, completed by 27 students from eight health-related courses. Data were analyzed using Bernard Charlot’s analysis technique. Four categories of learning were identified: generic, relational and intersubjective, professional training-related, and contextual/situational, along with the identification of learning agents and places. The results highlight the potential of interprofessional education during undergraduate studies as a promoter of collaborative practices, knowledge sharing, active listening, and teamwork, contributing to a critical, comprehensive, and aligned training with the guidelines of the Brazilian Unified Health System. The study reinforces the importance of interprofessional training in higher education, mediated by meaningful experiences in the territory, capable of reshaping the educational process and strengthening the integration between education, service, and community.